Two new species of Dichelyne Jägerskiöld, 1902 (Nematoda: Cucullanidae) parasitising marine fishes in Iraq - Fazaa, Hassan A; Moravec, František; Ali, Atheer H; Saud, Hussein A (Systematic parasitology, 2023)
Recent examinations of some marine fishes from off the southern coast of Iraq revealed the presence of two new species of Dichelyne (Dichelyne) Jägerskiöld, 1902 (Nematoda: Cucullanidae), both intestinal parasites, namely: D. (D.) lethrini n. sp. from the smalltooth emperor Lethrinus microdon Valenciennes (Lethrinidae, Acanthuriformes) and D. (D.) iraqiensis n. sp. from the humphead snapper Lutjanus sanguineus (Cuvier) (Lutjanidae, Acanthuriformes). Specimens are described and illustrated based on light and scanning electron microscopical examinations. Dichelyne (D.) lethrini n. sp. is mainly characterised by the length of spicules (522 µm), presence of a dorsal caecum, location of deirids at the level of the posterior end of oesophagus and the post-oesophageal position of the excretory pore, number (10 pairs) and distribution of caudal papillae in the male, and the presence of two minute terminal spines on the female tail tip. Dichelyne (D.) iraqiensis n. sp. differs from the species of the subgenus Dichelyne mainly based on the absence of caudal spines, the presence of a dorsal caecum, the length of spicules (789-884 µm), the location of deirids and the excretory pore approximately at the same level, and the size of eggs (72-78 × 42-51 µm). These new species infecting marine fishes in Iraq represent new geographic records of cucullanids of the subgenus Dichelyne from fishes in marine waters off Iraq.
Keywords: hlístice; druhová specificita; Perciformes; Male; Fish Diseases; Nematoda; Ascaridida; mužské pohlaví; Species Specificity; ryby; Fishes; Animals; Iraq; ženské pohlaví; Microscopy, Electron, Scanning; zvířata; nemoci ryb; Irák; Female; mikroskopie elektronová rastrovací